Influence Of Leadership Style And Motivation To Work Employee Job Satisfaction (Case study at Pt Inovasi Teknologi) - Melvin S Sarsale; Abd. Rasyid Syamsuri (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study was to identify and analyze the influence of motivation work against leadership style and job satisfaction of employees at PT Technological Innovation. This research was conducted by technik simple random sampling (simple sampling technique), with a sample of 75 respondents. Entire multiple regression equation used meets the requirements of the classical assumption test. The results of this study indicate that there is a significant and positive influence between leadership style and motivation simultaneously on employee job satisfaction in PT Technological Innovation.